Fa’ āliyyatu Istikhdām Kitāb Metode Praktis Belajar Ilmu Shorof Untuk Pemula Litarqiyyati Mahāroh Al Qirō’ah Litthullābi Al Faslu Al Rōbi’ Al Ibtidā’i - Segaf Baharun; Fawwazul Farisi (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
The problems that researchers found occurred in this school are most of the students were not able to understand the reading well, because there are reasion. firstly, to the lack of memorized vocabulary, secondly, not knowing the grammatical rules, and thirdly, not knowing the morphological rules, so for this reason the researcher wanted to shed light on the importance of learning the science of morphology. The goals of this research are: (1) To understand the process of using the book of morphology for beginners by Professor Hassan Basri bin Muhammad to improve the reading skill (2) To understand effectiveness use of the book of morphology for beginners by Professor Hassan Basri bin Muhammad to improve the reading skill. The approach to this research is the quantitative approach.Data collection technique of this research are: (1) Observation, (2) Interview, (3) Test. The results of this research can be summarized as follows: The use of the book of morphology for beginners by Professor Hassan Basri bin Muhammad to improve the reading skills of fourth grade primary school students at the Dar Al-Lugha and Al-Da'wa Institute is effective because there are statistically significant differences from each side, as the value of T reached 4.360 for the experimental group greater than 2.257 for the control group.